Analisis Kinerja Keuangan dengan Metode Almant Z- Score pada PT.Terregra Asia Energy,Tbk - Ashari, Nala Oktaviani; Oktariani, Refi; Banjarnahor, Denisa Natalia (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the financial performance and predict the potential for bankruptcy at PT Terrega Asia Energy, Tbk using the Altman Z-Score model. This study uses a descriptive approach by utilizing secondary data in the form of PT Terrega Asia Energy, Tbk's financial statements for the 2020-2022 period, which can be accessed through the Indonesia Stock Exchange (IDX) website at https://www.idx.co.id/ and other official sources. The analysis is carried out by calculating and interpreting financial ratios including liquidity, profitability, leverage, and activity. The Z-Score model is used as a predictive tool for potential bankruptcy based on certain financial ratios. This analysis is expected to serve as a reference for management in identifying financial risks and formulating improvement strategies. Furthermore, the Z-Score is calculated based on the Altman formula to determine the company's financial health. The results of the analysis show that PT Terrega Asia Energy Tbk is in the "safe" zone with a Z-Score value above 2.6 and 2.99. This indicates that PT Terrega Asia Energy, Tbk has a healthy financial condition and is unlikely to experience bankruptcy in the short term.